Cartografia geomorfológica: estudo da urbanização na bacia hidrográfica do rio Tigre, Erechim, RS - Furlan, André Ricardo (2023)
The field of geographical studies presents several purposes, among which is Geomorphology, which aims to understand landforms, their genesis, and past and present processes. With the gradual increase in urbanized areas across the globe, Geomorphology and geomorphological cartography, in addition to understanding natural processes, have also begun to consider human actions as geomorphological agentes. To concisely evaluate the effects of human action, the analytical unit used corresponds to the watershed. This allows for the identification of modifications in hydrogeomorphological behavior, aiding in environmental planning and land management. Therefore, the main objective of the thesis is to recognize and evaluate, through geomorphological cartography, the expansion of anthropogenic interventions in the Tigre River watershed located within the urban area of Erechim, Rio Grande do Sul. As a refinement to the desk research data, fieldwork was conducted, which was incorporated across all mapping phases. Through the analysis of the original morphology, nine distinct relief elements were identified, each exhibiting unique characteristics, alongside the recognition of three types of valleys. On the other hand, the anthropogenic morphology displays three stages of urbanization, accompanied by cuttings, landfills, road development, and marks left by mining activities. Additionally, noticeable alterations include canal infilling and straightening, along with water retention areas represented by reservoirs. The impact of the urbanization process on the morphology of the hydrographic basin is evident, particularly in the years 1975, 1989, 2010, and 2023. Urbanization in the hydrographic basin reached 35.43% in 1975, 64.14% in 1989, 75.86% in 2010, and by 2023, it covered an area of 79.22% of the hydrographic basin. The formulation of evolutionary cartographic documents representing different stages of urbanization provided a comprehensive view of the morphological changes and hydrographic dynamics in the basin over a period of 48 years. It is evident that the lack of proper environmental planning in the basin exposes the population to the risk of flooding, resulting in various disruptions.